Tyrosine-O-sulfation is a widespread affinity enhancer among thrombin interactors. (28th February 2022) - Ripoll-Rozada, Jorge; Maxwell, Joshua W. C.; Payne, Richard J.; Barbosa Pereira, Pedro José
Abstract : Tyrosine- O -sulfation is a common post-translational modification (PTM) of proteins following the cellular secretory pathway. First described in human fibrinogen, tyrosine- O -sulfation has long been associated with the modulation of protein–protein interactions in several physiological processes. A number of relevant interactions for hemostasis are largely dictated by this PTM, many of which involving the serine proteinase thrombin (FIIa), a central player in the blood-clotting cascade. Tyrosine sulfation is not limited to endogenous FIIa ligands and has also been found in hirudin, a well-known and potent thrombin inhibitor from the medicinal leech, Hirudo medicinalis . The discovery of hirudin led to successful clinical application of analogs of leech-inspired molecules, but also unveiled several other natural thrombin-directed anticoagulant molecules, many of which undergo tyrosine- O -sulfation. The presence of this PTM has been shown to enhance the anticoagulant properties of these peptides from a range of blood-feeding organisms, including ticks, mosquitos and flies. Interestingly, some of these molecules display mechanisms of action that mimic those of thrombin's bona fide substrates.